Perencanaan Tempat Pengolahan Sampah Reduce, Reuse, Recycle Menggunakan Black Soldier Fly di Desa Karyamulya Kabupaten Ciamis - Melly Mellyanawaty; Hendrik Iskandar; Estin Nofiyanti; Nurcholis Salman (Fakultas Teknik, 2021)
Solid waste known as garbage still becomes one of the most concerning issues in Indonesia. It increases every year; however, the landfill was not expanded. The accumulation of garbage could give a negative impact on the environment and health. Due to this reason, there is an alternative suggested to reduce the garbage and its sources. The initiative called ‘Bank sampah’, itis a garbage treatment system which is managed by the community. In addition, the Reduce, Reuse, Recycle (3R) laystall was built to carry out some ‘Bank Sampah’. This study conducted a preliminary design of 3R laystall at Desa Karyamulya Kecamatan Cisaga Kabupaten Ciamis. The design of the 3R laystall using black soldier fly method to decompose organic materials is employed in this research. The quantity and the density of the garbage were required to determine the design of the lay stall. Stratified random sampling was conducted for 8 days. Desa Karyamulya generates 2.361 liters/person/day or 0.236 kg/person/day. According to a population projection for the next 10 years, the estimation of garbage composition consists of food waste (52.15%); plastic (23.58%); paper (9.23%); fabric (0.45%); wood/leaf (6.38%); diapers (2.85%); metal (0.94%); rubber/leather (2.19%); glass (0.17%); and styrofoam (2.04%). From the quantity and composition of the garbage, it requires approximately 94 m2 of the area and an estimated funds needed as Rp. 483.908.600